Using Electronic Interaction as an Educational Support Tool in Higher Education: Studentsâ€™ Perception on using M-Learning and the Lecturersâ€™ Reflections - Rooyen, Hannelie Van (Journal of Education and Vocational Research, 2014)
Teaching and learning in higher education must be transformed to give support to the new generation of â€œdigital nativeâ€ students. Students depend on their mobile phones to do almost everything. The purpose of this research is to determine the perception of students on using mobile phones as an educational supporting tool and discusses higher education challenges and benefits of using electronic communication as an educational supporting tool. Most students use their mobile phones daily and they enjoy the technology that mobile phones offer them. The research was conducted at Vaal University of Technology (VUT) Ekurhuleni Campus. The findings of the research indicate that electronic communication will have a positive impact. Currently, more students have access to mobile phones than computers. Mobile phones can thus be considered an enabling technology in supporting learning and teaching. This research has provided a basis for VUT and other higher learning institutionsâ€™ academic leaders to start the discussion and the possibility of introducing the use of m-learning in adult education. With the increasing use of electronic communication, the traditional teaching approach and interaction between the lecturer and student(s) is changing and the adoption of friendly electronic communication has become more important.